A Case Study of EFL Learners’ Difficulties in Listening Comprehension - Wahidah, Farah Sukmawati (Universitas Swadaya Gunung Jati, 2018)
This research tries to analyse the students’ level of difficulty in listening comprehension and the factors causing it. This is a case study research. This research revealed that students had many difficulties in listening comprehension. The difficulties from the biggest percentage were understanding organization, pragmatic understanding, and basic comprehension. Then, there were many factors causing students’ difficulties in listening. The factors were from the speaker, the environment, and the speaker itself. The factors causing the difficulties from the biggest percentage were the environment (noisy), poor recording, unfamiliar topics, accent of the speaker, ungrammatical sentences, long listening, concentration or focus, unknown words, uninteresting topic, and recognizing main points. Keyword: listening difficulties, factors causing listening difficulties.